Нелинейные нормальные формы параметрических колебаний - Аврамов, К.В. (Видавничий дім "Академперіодика" НАН України, 2008)
An iterative procedure combining the Rausher approach and nonlinear modes is suggested to analyze nonlinear systems with parametric terms. The example of the application of this method to the analysis of beam parametric vibrations interacting with a discrete oscillator is considered.